FAKTOR DOMINAN YANG MEMPENGARUHI PEMBERIAN ASI EKSKLUSIF DI POSYANDU MAWAR 1 PUSTU PRADAH PUSKESMAS DUKUH KUPANG SURABAYA - YUSTINA, BUDI, YUSTINA, BUDI (D3 Kebidanan, 2012)
Exclusive breastfeeding is the only breast-fed infants without additional food such as water, milk, honey and other food and administered to infants 6 months of age. As for the factors that influence exclusive breastfeeding among others, changes in socio-cultural factors, psychological factors, psychological factors, physical factors, economic factors, factors of family support, and knowledge factors. Purpose of the study to determine the dominant factors affecting exclusive breastfeeding in the IHC Health Center Rose 1 Pradah Hamlet Kupang Surabaya. The study design used was descriptive. Samples were taken from mothers who had infants aged <1 year as many as 28 respondents, the sampling means using a purposive sampling. Based on the factors influencing the results showed that exclusive breastfeeding cultural factors of social change as many as 20 people (71%), psychological factors as many as 27 people (96%), physical factors as many as 27 people (96%), economic factors as much as 28 people (100% ), the factor of family support as many as 23 people (82%), and the knowledge factor as many as 24 people (86%). Of the six factors above the dominant factor affecting exclusive breastfeeding in the Rose 1 IHC Health Center Hamlet is the economic factor. This can be due to mothers who do not work tend to give exclusive breastfeeding because it has a lot of time together with his son, otherwise it can save the cost of household expenses. While working mothers have less time with their children, and busy with his work. Therefore, they tend to give formula instead of Exclusive Breastfeeding.Key words: Exclusive breastfeeding, economic factors.